Effect of Macrophytes on Flow Conditions and Deposition of Suspended Particles in Small Streams: an Experimental Study Using Artificial Vegetation - Rolland, Delphine; Haury, Jacques; Marmonier, Pierre; Lagadeuc, Yvan (Revue des sciences de l’eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2015)
AbstractAquatic macrophytes are often the dominant element that influences flow conditions within streams, and are often considered as ecosystem engineers that modify their aquatic environment as a result of their physical structure and metabolic activity. The role of aquatic macrophytes on suspended matter sedimentation was studied in three shallow low-order streams in Brittany (North-western France). Field experiments were carried out in April 2007 using Callitriche-like artificial macrophytes and cylindrical sediment traps dug into the channels. Hydrodynamic characteristics (velocity profile, percentage of velocity decrease and turbulence), volume of trapped sediment, particle size characteristics, and total organic matter content were measured within the macrophytes and compared with the control traps. The aquatic macrophytes operated as sediment traps by modifying the local hydrodynamic parameters. Sedimentation of fine suspended particles within the macrophytes reached maximum values when the velocity was significantly reduced, i.e. when the initial velocity was low (less than 0.5 m∙s‑1) and the depth shallow enough for the plant to occupy the entire volume of the column water. Conversely, turbulence was generated around the macrophyte stands, which induced the resuspension of fine particles and only coarse particles were trapped. This study shows the importance of threshold values at the local scale and the highly dynamic effect of macrophytes on flow characteristics.